Sharpening those tools - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In the field of agricultural policy networking, a high-level seminar was held in Entebbe, Uganda, from 6 to 10 November 2000